2022
DOI: 10.36660/ijcs.20210286
|View full text |Cite
|
Sign up to set email alerts
|

Are Wistar Rats the Most Suitable Normotensive Controls for Spontaneously Hypertensive Rats to Assess Blood Pressure and Cardiac Structure and Function?

Abstract: The first animal models of hypertension involved constriction of renal arteries (the Goldblatt kidney) or parenchyma (the Page kidney). Although these human analogs closely mimicked the pathophysiology of the disease, renovascular hypertension and the Page kidney represent only a small fraction of human hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Despite the fact that SHR and WKY rats are genetically related, WKY are a more heterogenous strain compared with SHR. In this regard, it appears that the distributed SHR have been fully inbred (i.e., after 20 generations of brother-sister mating), whereas the breeding stocks of WKY had been distributed before full inbreeding [ 31 ]. Accordingly, the biological variability of WKY may be greater than that of SHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that SHR and WKY rats are genetically related, WKY are a more heterogenous strain compared with SHR. In this regard, it appears that the distributed SHR have been fully inbred (i.e., after 20 generations of brother-sister mating), whereas the breeding stocks of WKY had been distributed before full inbreeding [ 31 ]. Accordingly, the biological variability of WKY may be greater than that of SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WKY rats had earlier reductions in cardiac function when compared with Wistar rats. Due to these factors, some authors have actually used or suggested the use of Wistar rats as a control for SHR in several conditions [ 31 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental animals were male Wistar rats (Experimental Medicine Center, Lublin, Poland) weighing 150-200 g and aged 7 weeks, which were kept under standard laboratory conditions (12 h light-dark cycle, standard humidity and temperature 21 • C ± 1 • C), with food and water available without limits. Wistar rats are widely used in cardiovascular and metabolic research [27], mainly due to their normalized blood pressure [28]. Males were tested in our study to reduce the potential impact of hormonal variation compared to female rats.…”
Section: Animalsmentioning
confidence: 99%